Profile of the Ovation ALTO abdominal stent graft for the treatment of abdominal aortic aneurysms: overview of its safety and efficacy. (2nd December 2021) - Gregory, Mark; Metcalfe, Matt; Steiner, Kate
ABSTRACT: Introduction: The Ovation ALTO is the next generation aortic stent graft from Endologix for the treatment of infra-renal abdominal aortic aneurysms. The device uses polymer-injected rings to create a proximal seal at the aneurysm neck. Areas Covered: Results from the first clinical study of the ALTO graft are analyzed and the potential benefits of the graft in minimizing post-treatment aneurysmal neck dilation discussed. The implications of the ALTO's Instructions-For-Use (IFU) and low-profile delivery system are also reviewed. Expert Opinion: The re-positioning of the sealing rings higher on the graft and an integrated compliant balloon are the most significant improvements on the Ovation iX, facilitating accurate placement of the proximal sealing ring and prompt balloon dilation of the polymer rings. The expansion the IFU to include neck lengths of ≥7 mm will mean more patients are eligible for infra-renal EVAR within IFU with the ALTO device. The published data on the device to date is limited. With over 1000 implants worldwide we would hope for more published data to become available. If this demonstrates similar mid-term results to that seen with the Ovation iX in arguably more hostile neck anatomy, then the Ovation ALTO is likely to be more widely used.